Betaine Attenuates Osteoarthritis by Inhibiting Osteoclastogenesis and Angiogenesis in Subchondral Bone - Yajun, Wang; Jin, Cui; Zhengrong, Gu; Chao, Fang; Yan, Hu; Weizong, Weng; Xiaoqun, Li; Qirong, Zhou; Huiwen, Chen; Hao, Zhang; Jiawei, Guo; Xinchen, Zhuang; et al. (Frontiers in Pharmacology, 2021)
Osteoarthritis (OA) is the most common type of arthritis with no effective therapy. Subchondral bone and overlying articular cartilage are closely associated and function as “osteo-chondral unit” in the joint. Abnormal mechanical load leads to activated osteoclast activity and increased bone resorption in the subchondral bone, which is implicated in the onset of OA pathogenesis. Thus, inhibiting subchondral bone osteoclast activation could prevent OA onset. Betaine, isolated from the Lycii Radicis Cortex (LRC), has been demonstrated to exert anti-inflammatory, antifibrotic and antiangiogenic properties. Here, we evaluated the effects of betaine on anterior cruciate ligament transection (ACLT)-induced OA mice. We observed that betaine decreased the number of matrix metalloproteinase 13 (MMP-13)-positive and collagen X (Col X)-positive cells, prevented articular cartilage proteoglycan loss and lowered the OARSI score. Betaine decreased the thickness of calcified cartilage and increased the expression level of lubricin. Moreover, betaine normalized uncoupled subchondral bone remodeling as defined by lowered trabecular pattern factor (Tb.pf) and increased subchondral bone plate thickness (SBP). Additionally, aberrant angiogenesis in subchondral bone was blunted by betaine treatment. Mechanistically, we demonstrated that betaine suppressed osteoclastogenesis in vitro by inhibiting reactive oxygen species (ROS) production and subsequent mitogen-activated protein kinase (MAPK) signaling. These data demonstrated that betaine attenuated OA progression by inhibiting hyperactivated osteoclastogenesis and maintaining microarchitecture in subchondral bone.